Transpiration from subarctic deciduous woodlands: environmental controls and contribution to ecosystem evapotranspiration ... - Rafael Poyatos; Ana M. Sabater; Helen C. Ward; Timothy C. Hill; Jemma L. Gornall; Thomas J. Wade; Jonathan G. Evans; Ana Prieto-Blanco; Mathias Disney; Gareth K. Phoenix; Mathew Williams; Brian Huntley; et al. (Zenodo, 2019)
Data from the paper: Sabater, AM, Ward, HC, Hill, TC, et al. Transpiration from subarctic deciduous woodlands: Environmental controls and contribution to ecosystem evapotranspiration. Ecohydrology. 2020; 13:e2190. https://doi.org/10.1002/eco.2190 ...